FIGURE 13 in Bivalves from the latest Jurassic-earliest Cretaceous hydrocarbon seep carbonates from central Spitsbergen, Svalbard - Hryniewicz, Krzysztof; Little, Crispin T.S.; Nakrem, Hans Arne (Zenodo, 2014)
FIGURE 13. (A–J) Tehamatea rasmusseni sp. nov. (A) Lateral view of holotype showing the vertical valve displacement. (B) Detail for interior of right valve showing cardinal dentition. Note long lunule, small 3a and long 3b. (C) Lateral view of exterior of right valve showing oval outline and ornament of dense commarginal growth lines. (D–E) Silicone rubber casts of right valve cardinal areas showing small 3a and large, thick 3b cardinal teeth. (F) Oblique lateral view of a right valve internal mould showing small anterior and posterior lateral teeth. (G) Lateral view right valve internal mould showing shapes and relative sizes of anterior and posterior adductor muscle scars and wavy pallial line below anterior adductor muscle scar, representing possible mantle lobe scars. (H) Silicone rubber cast of an articulated internal mould showing anterior adductor muscle scar and anterior lateral teeth. (I) Dorsal view of an articulated shell showing long external ligament, flattened posterior shell area and deep, lancet-shape, slightly asymmetric lunule. (J) Lateral view of a right valve internal mould showing bioimmuration trace. (K–N) Cretaxinus hurumi gen. et sp. nov. (K) Lateral view of articulated holotype left valve showing shell outline. Note very weakly sulcated posterodorsal margin extending only slightly above the shell outline. (L) Holotype anterior view showing large and deep lunule. (M–N) Holotype posterior and dorsal views respectively, showing external portion of the ligament, escutcheon and posterodorsal margin sulcation. (A–B) PMO 217.234, (C) PMO 217.169, (D) PMO 217.173, (E) PMO 217.243, (F) PMO 225.111, (G) PMO 225.104, (H) PMO 225.101, (I) PMO 217.227, (J) PMO 217.247, (K–N) PMO 217.277. Scale bars 10 mm. : Published as part of Hryniewicz, Krzysztof, Little, Crispin T.S. & Nakrem, Hans Arne, 2014, Bivalves from the latest Jurassic-earliest Cretaceous hydrocarbon seep carbonates from central Spitsbergen, Svalbard, pp. 1-66 in Zootaxa 3859 (1) on page 33, DOI: 10.11646/zootaxa.3859.1.1, http://zenodo.org/record/4930112